2015
DOI: 10.1016/j.neuropsychologia.2015.04.016
|View full text |Cite
|
Sign up to set email alerts
|

Time, number and attention in very low birth weight children

Abstract: Premature birth has been associated with damage in many regions of the cerebral cortex, although there is a particularly strong susceptibility for damage within the parieto-occipital lobes (Volpe, 2009). As these areas have been shown to be critical for both visual attention and magnitudes perception (time, space, and number), it is important to investigate the impact of prematurity on both the magnitude and attentional systems, particularly for children without overt white matter injuries, where the lack of o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 65 publications
(89 reference statements)
0
15
2
Order By: Relevance
“…Gebuis and Reynvoet ( 2011 ) proposed that five visual properties of the numerosity comparison task could affect numerosity comparison: total surface area, envelope area or convex hull, item size, density, and circumference. Density is defined as the number of items per unit area (e.g., Anobile et al, 2013a ; Tinelli et al, 2015 ). Zhou et al ( 2015 ) showed that the numerosity comparison task was still ratio-dependent after the five visual properties of dot arrays were controlled for.…”
Section: Methodsmentioning
confidence: 99%
“…Gebuis and Reynvoet ( 2011 ) proposed that five visual properties of the numerosity comparison task could affect numerosity comparison: total surface area, envelope area or convex hull, item size, density, and circumference. Density is defined as the number of items per unit area (e.g., Anobile et al, 2013a ; Tinelli et al, 2015 ). Zhou et al ( 2015 ) showed that the numerosity comparison task was still ratio-dependent after the five visual properties of dot arrays were controlled for.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, dyscalculic children have often been found to have poorer numerosity thresholds (Mazzocco, Feigenson, & Halberda, 2011;Piazza et al, 2010) -but see also Rousselle and Noel (2007) for a different account. Besides, the investigation of numerosity perception is expanding to other developmental disorders like autism , motor coordination disorders (Gomez et al, 2015) and preterm children (Hellgren, Halberda, Forsman, Ådén, & Libertus, 2013;Tinelli et al, 2015).…”
Section: Items Connection Affects Ans and Texture-density 140mentioning
confidence: 99%
“…In contrast, performance IQ and verbal IQ, and vocabulary scores, did not differ from the norms. Tinelli et al (2015) have also reported an attention deficit among 29 preterm born children (who were without identified brain lesions on ultrasound) in a motion-related task, the multiple-object tracking test.…”
Section: Introductionmentioning
confidence: 98%